Fluorine-18 fluorodeoxyglucose positron emission tomography imaging of T-lymphoblastic lymphoma patients - Park, Jong Hoon (Oncol Lett, 2016)
The purpose of the present study was to evaluate the fluorine-18 fluorodeoxyglucose positron emission tomography (FDG-PET) findings in patients with T-lymphoblastic lymphoma (T-LBL). In total, 9 patients with histopathologically confirmed T-LBL were included in the study. Bone marrow (BM) involvement and leukemic transformation (LT) were evaluated through iliac crest marrow biopsy and peripheral blood blast count. FDG-PET scans were performed at the initial pre-treatment point. Two experienced nuclear medicine physicians evaluated the FDG-PET images by visual analysis and using the maximum standardized uptake values (SUVmax) of the malignant lesions. Overall, 8 out 9 patients presented with BM involvement; 7 showed LT, while 1 showed BM involvement without LT. All involved T-LBL lesions were FDG-avid with variable uptake. The mean SUVmax was 6.4±3.3. T-LBL patients with BM involvement showed diffuse or nodular marrow uptake. In addition, all the patients with LT showed diffuse marrow FDG activity. However, the patient with BM involvement but no LT showed nodular FDG uptake in the marrow. In conclusion, the present study indicates that it is possible to use FDG-PET for the evaluation of the disease extent of T-LBL. Furthermore, the imaging technique could provide a diagnostic clue for determining BM involvement or LT.